Farmer’s Perception on Impact of Climate Change on Mandarin (Citrus reticulata Blanco.) Production in Syangja, Nepal - KC, Mamita; KC, Subarna; Chaulagai, Bibas; Lamsal, Ganesh (International Journal of Applied Sciences and Biotechnology, 2025)
Research on “Farmer’s Perception on Impact of Climate Change on Mandarin (Citrus Reticulata Blanco.) Production In Syangja, Nepal” was conducted in 2024, under the guidance of PMAMP, Syangja. Altogether 120 households from Bhirkot and Putalibazzar municipalities were selected randomly for the study. Primary data were obtained from face-to-face interview schedule, Focus Group Discussion, Key Informant Interview and secondary data from Department of Hydrology and Meterology (DHM), Kathmandu, and several publications. Majority of the farmers perceived the change in climatic condition in terms of increase in temperature and decrease in rainfall which brings a prolonged drought leads to loss in production. Analysis of the climatic data (last 30 years for rainfall and temperature) showed the increasing trend for maximum and minimum 0.0768°C per year and 0.003°C per year respectively and decreasing trend of mean annual precipitation is -0.1762 mm per year. The major natural hazards for mandarin production were prolonged drought during flowering and fruit setting time, followed by heavy hailstorm, storm, soil-erosion, frost, and landslide respectively, resulting downward trend in mandarin yield in study area. Farmers in the study area are mostly practiced mulching as an adaptation strategy to combat impacts of climate change against drought. The study concluded that farmers experienced the climate change, and its negative impact too, but haven’t taken any adaptation measures to mitigate its effect. So, there is immediate need of effective adaptation mechanisms to make country self-sufficient in Mandarin production. Int. J. Appl. Sci. Biotechnol. Vol 13(1): 23-30.